Associations between Parental Engagement in the Neonatal Intensive Care Unit and Neighborhood-Level Socioeconomic Status - Wallace, Lisa S.; Okito, Ololade; Mellin, Kelsi; Soghier, Lamia (American Journal of Perinatology, 2024)
Objective This study aimed to (1) determine the effect of neighborhood-level socioeconomic status (SES), which considers the social and physical environment where a person lives, on parental engagement in the Neonatal Intensive Care Unit (NICU) and (2) compare the relationships between parental engagement and individual versus neighborhood-level measures of SES.Study Design In this cohort study, parents (n = 45) of premature neonates ≤34 weeks' gestation were assessed at 2 and 6 weeks after birth from December 2017 to October 2019. Neighborhood-level SES was determined using census data per the Association of Maternal and Child Health Programs' methodology, and parents self-reported their education level as an individual-level measure of SES. Data on frequency of engagement in NICU activities, including telephone updates, visitation, providing expressed breastmilk, and participating in kangaroo care, were collected from the electronic medical record. Parent psychosocial factors were assessed using validated surveys. Statistical analysis was performed using Fisher's exact test, t-test, and logistic regression.Results In multivariate regression analysis, disadvantaged neighborhood-level SES was associated with decreased odds of kangaroo care (OR = 0.16, 95% CI: [0.03–0.89]) and visitation (OR = 0.14, 95% CI: [0.02–0.87]), while lower individual-level SES was not significantly associated with kangaroo care, visiting, calling, or pumping (p > 0.05).Conclusion Parental engagement was more consistently and significantly associated with neighborhood-level SES than with individual-level SES. Therefore, neighborhood-level SES measures may be more explanatory than individual-level SES measures. Further studies and targeted interventions are needed to address disparities in the frequency of kangaroo care and visitation according to SES.Key Points
Keywords: prematurity; breastfeeding; kangaroo care; parent visitation; social determinants of health; neighborhood disadvantage